SCHOOL-BASED ASSESSMENT RESEARCH IN FIVE NATIONS - Sattler, Jerome M.; Saigh, Philip A. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1990)
This special issue of the McGill Journal of Education is devoted to school-based assessment research in Canada, People’s Republic of China, Israel, Lebanon, and the United States. The focus of each paper is primarily on psychoeducational assessment issues that involve standardized intelligence, achievement, and personality/temperament tests used to evaluate children having difficulties in school. The nations surveyed are located in North America, the Middle East, and China. Readers, therefore, will be able to gain some understanding of current trends in psychoeducational assessment research in diverse regions of the world.